2010
DOI: 10.1107/s0907444910023723
|View full text |Cite
|
Sign up to set email alerts
|

Emerging from pseudo-symmetry: the redetermination of human carbonic anhydrase II in monoclinicP21with a doubledaaxis

Abstract: PDB Reference: human carbonic anhydrase II, 3mwo.The crystal structure of human carbonic anhydrase II in the monoclinic P2 1 space group with a doubled a axis from that of the usually observed unit cell has recently been reported, with one of the two molecules in the asymmetric unit demonstrating rotational disorder [Robbins et al. (2010), Acta Cryst. D66, 628-634]. The structure has been redetermined, with the coordinates of both pseudosymmetrically related molecules in the crystallographic asymmetric unit tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Unexpectedly, however, the P2 1 space-group symmetry of the simpler crystal form was also broken under the most obvious choice of origin for the doubled unit cell, leading to apparent disorder. The correct structure, which was fully ordered, was obtained in retrospect when it was found that shifting the origin of the doubled unit cell led to recovery of the required symmetry elements in P2 1 (Robbins et al, 2010a). Likewise, in our study, the shifting of a second hexagonal layer relative to the first layer breaks the P6 symmetry that would have been present in a single layer, leaving what appears to be P3 symmetry under the original choice of unit cell (Fig.…”
Section: Broken Crystallographic Symmetry Often Requires a New Choicesupporting
confidence: 54%
“…Unexpectedly, however, the P2 1 space-group symmetry of the simpler crystal form was also broken under the most obvious choice of origin for the doubled unit cell, leading to apparent disorder. The correct structure, which was fully ordered, was obtained in retrospect when it was found that shifting the origin of the doubled unit cell led to recovery of the required symmetry elements in P2 1 (Robbins et al, 2010a). Likewise, in our study, the shifting of a second hexagonal layer relative to the first layer breaks the P6 symmetry that would have been present in a single layer, leaving what appears to be P3 symmetry under the original choice of unit cell (Fig.…”
Section: Broken Crystallographic Symmetry Often Requires a New Choicesupporting
confidence: 54%
“…High-resolution crystal structures of CA II appeared later and helped to understand the water network in the active site (Fisher et al, 2007a;Avvaru et al, 2010b). There was also some variability in crystal forms of CA II, first mentioned by Robbins et al (2010).…”
Section: Ca IImentioning
confidence: 99%
“…There was also some variability in crystal forms of CA II, first mentioned by Robbins et al . (2010).…”
Section: X-ray Crystallographic Studies Of Human Ca Isoformsmentioning
confidence: 99%
“…Pletnev and coworkers named this disorder a 'rotational order-disorder structure'. In addition, the structure of human carbonic anhydrase was first identified as a rotational order-disorder structure (Robbins et al, 2010a); however, this identification was later corrected and refined as a structure with an alternative selection of molecules in the asymmetric unit (Robbins et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%